The Influence of Job Satisfaction on the Performance of Madrasah Aliyah (Islamic Senior High School) Teachers - Mesiono, Mesiono (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2019)
The quality of education is strongly influenced by teacher performance. One factor that supports the improvement of teacher performance is job satisfaction. When job satisfaction is high, it will affect job performance and achieve goals optimally. This study aims to determine the effect of job satisfaction on teacher performance in the state Islamic Senior High School in Medan, Indonesia. The research method used is quantitative methods with a sample of 45 teachers taken from Madrasah Aliyah Negeri 3 Medan. Data analysis was performed using a t-test with a significance level of 95 %. Based on the test result, it is obtained that tcount > ttable. This shows that there is a significant correlation between job satisfaction and teacher performance. Based on the analysis results, it is concluded that job satisfaction is one of the factors that increase teacher performance where the higher the job satisfaction, the better and the performance of the teachers. This study provides recommendations for educational policyholders to increasingly pay attention to the factors that can increase teacher job satisfaction in state Islamic High School public in particular or other educational institutions in general.